Analisis Durasi Jam Kerja dengan Low Back Pain pada Nelayan di Dusun Mamokeng Negeri Tulehu Kecamatan Salahutu Kabupaten Maluku Tengah - Tunny, Hasna; Rochmaedah, Siti; Soamole, Idham; Lombonaung, Ellen (Sekolah Tinggi Ilmu Kesehatan Widya Dharma Husada Tangerang, 2023)
Background: Low back pain (LBP) is a condition with discomfort or acute pain in the lower back in the fifth and sarcoid lumbar vertebrae. Low back pain (LBP) is the most common musculoskeletal disorder in the world. About 80% of adults will experience low back pain in their lifetime.One of the main causes of low back pain is moderate to vigorous physical activity. High physical activity has become a risk factor for low back pain, especially in adolescents and adults. In the adolescent to adult age group, a person has higher and heavier activities compared to children and the elderly.Activities carried out can be in the form of playing, exercising, working, and also studying. Objective: To determine the relationship between work duration and low back pain in fishermen from Mamokeng Village.Method: The implementation of this activity is carried out face to face from house to house with the aim of making it more effective, convincing and familiarizing the relationship between the researcher and the target as well as a quick response. Results: There is a relationship between the duration of working hours and lower back pain in fishermen in Mamokeng Negeri Tulehu Hamlet with p = 0.001. Suggestion: It is hoped that fishermen from Mamoken Village can reduce the duration of their work so that their health is maintained. ABSTRAK Latar Belakang: Low back pain (LBP) merupakan suatu keadaan dengan rasa tidak nyaman atau nyeri akut pada punggung bawah daerah ruas lumbalis kelima dan sarkalis, Low back pain (LBP) kelainan musculoskeletal yang paling umum di dunia. Sekitar 80% orang dewasa akan mengalami low back pain di masa hidupnya. Salah satu penyebab utama dari low back pain adalah aktivitas fisik sedang hingga tinggi. Aktivitas fisik yang tinggi telah menjadi faktor risiko low back pain terutama pada remaja hingga dewasa. Pada kelompok umur remaja hingga dewasa, seseorang memiliki aktivitas yang lebih tinggi dan berat dibanding dengan anak-anak maupun lansia. Aktivitas yang dilakukan dapat berupa bermain, berolahraga, bekerja, dan juga belajar. Tujuan: Untuk mengetahui hubungan antara durasi kerja terhadap nyeri punggung bawah pada nelayan dusun mamokeng. Metode: Pelaksanaan kegiatan ini dilakukan secara langsung bertatap muka dari rumah ke rumah dengan sasaran sehingga lebih efektif, meyakinkan dan mengakrabkan hubungan antara peneliti dan sasaran serta cepatnya respon. Hasil: Terdapat hubungan antara durasi jam kerja dengan nyeri punggung bawah pada nelayan di Dusun Mamokeng Negeri Tulehu dengan nilai p=0.001. Saran: Diharapkan nelayan Desa mamoken dapat mengurangi durasi kerjanya sehingga kesehatannya tetap terjaga.